1983
DOI: 10.1104/pp.72.4.959
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Inner Membrane-Associated and Matrix NAD-Specific Isocitrate Dehydrogenase in Potato Mitochondria

Abstract: The isotherm for isocitrate oxidation by potato (Solanum tuberosum L.var. Russet Burbank) mitochondria in the presence of exogenous NAD is characterized by a hyperbolic phase at isocitrate concentrations below 3 millimolar, and a sigmoid, or positively cooperative phase from approximately 3 to 30 mllmlar. The two forms of isocitrate dehydrogenase were separated and characterized following the sonication of mitochondria in 15% glycerol in the absence of buffer, followed by fractionation in a density step gradie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
22
0

Year Published

1983
1983
1995
1995

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 23 publications
4
22
0
Order By: Relevance
“…3). The pH optimum of 7.8 for NAD+-ICDH is in agreement with the literature (4,28). The pH of the cytosol has been determined to be about 7.5 with 31P NMR (25), and the pH in mitochondria is probably slightly higher.…”
Section: Comparison Of the Properties Of Nadp -And Nad -Icdhsupporting
confidence: 77%
See 1 more Smart Citation
“…3). The pH optimum of 7.8 for NAD+-ICDH is in agreement with the literature (4,28). The pH of the cytosol has been determined to be about 7.5 with 31P NMR (25), and the pH in mitochondria is probably slightly higher.…”
Section: Comparison Of the Properties Of Nadp -And Nad -Icdhsupporting
confidence: 77%
“…The co-operativity number was determined to be 3.9 using Hill plots. Co-operativity of NAD+-ICDH for isocitrate has previously been reported for pea (4) and potato (28) mitochondria, but with a Hill number of about 2.5.…”
Section: Comparison Of the Properties Of Nadp -And Nad -Icdhmentioning
confidence: 99%
“…On the other hand, inasmuch as freezing and thawing elicit a change akin to that caused by a drop in pH in the presence of NAD, while the isotherm remains sigmoid in the absence of NAD (data not shown), it would seem that it is the proposed membrane-bound ICDH that responds to the drop in pH and to freezing and thawing, respectively. The kinetics of the isolated membrane-associated enzyme reenforces this suggestion (23).…”
mentioning
confidence: 61%
“…The change in state being suggested is to be distinguished from the condensation of oligomeric subunits described by Hayman and Colman for NAD-linked ICDH (13). The isolation and characterization of the two potato enzymes have shown that they are indistinguishable when extracted at modest salt concentrations, but distinct, as in intact mitochondria, when extracted in the near absence of salt (23). Accordingly, the condition brought to mind is allotopy, wherein the characteristics of an enzyme are profoundly affected by the association of the enzyme with a membrane (19).…”
mentioning
confidence: 88%
“…The NAD+-specific ICDH has not been purified to homogeneity from a plant source, although some work has been done on the enzyme from peas (6-9, 11, 12) and potato (Solanum tuberosum) (17,20,21). Cox and Davies (7) man-Plant Physiol.…”
mentioning
confidence: 99%